Effect of Gargling of Young Coconut Water on Saliva pH of Elementary School Children in Batua Village, Makassar City - Syamsul Burhan (Newinera Publisher, 2020)
Various ways have been done to reduce the risk of caries including by utilizing a variety of plants and plants one of which is young coconut water. This study aims to determine the effect of gargling young coconut water on saliva pH, knowing the pH of saliva before and after gargling young coconut water and to determine the effect of gargling old coconut water on salivary pH. This research method is Pretest and Post-test research design. This study aims to examine the pH of saliva before and after treatment. Retrieval of data is done by purposive sampling technique. The results showed that gargling young coconut water could affect the pH of saliva, gargling young coconut water could reduce the pH of saliva, gargling young coconut water lowered the pH of saliva compared to gargling old coconut water. We recommend that you rinse water after consuming young coconut water or old coconut water.